Interaction between structural and geotechnical engineers - Katzenbach, Rolf; Turek, Jens (Thomas Telford, 2003)
This report has been prepared in the framework of the Co-operation in Science and Technology (COST) Action C7 for Soil-Structure Interaction in the Urban Civil Engineering. Based on a survey in 13 European countries and with additional input from the COST C7 members, the report focuses on several aspects effecting the interaction between structural and geotechnical engineers.